Professor at Large : The Cornell Years - Cleese, John (Book collections on Project MUSE., 2018)
"Comedian and actor John Cleese in the role of Ivy League professor at Cornell University, where he is currently professor-at-large. This book includes a selection of talks, essays, and lectures and provides a unique view of Cleese's endless pursuit of intellectual discovery across a range of topics"--